Strategies to improve electrochemical performances of pristine metal‐organic frameworks‐based electrodes for lithium/sodium‐ion batteries. (24th September 2021) - Liu, Zhoujia; Zheng, Fenfen; Xiong, Weiwei; Li, Xiaogang; Yuan, Aihua; Pang, Huan
Abstract: Metal‐organic frameworks (MOFs) have attracted considerable attention as promising next‐generation active electrode materials for lithium‐ion batteries (LIBs) or sodium‐ion batteries (SIBs) because of ultrahigh specific surface area, uniformly distributed pores, and tunable structure. However, there are some disadvantages inevitably far from meeting commercial requirements, such as low conductivity, inconvenient electron transmission, and unsatisfactory circulation stability. In this review, a comprehensive summary of MOFs‐based electrode materials is presented and discussed. First, the general Li + /Na + storage mechanism in MOFs‐based electrode materials, including conversion‐ and insertion‐type reactions, are summarized with details of active inorganic/organic ligands. Second, MOFs as anode materials for LIBs/SIBs are emphasized and improved on the electrochemical performances. Furthermore, very few research literature on MOFs‐based cathode materials is also discussed. Finally, opinions and prospects on the current challenge of MOFs‐based electrode materials are provided for future research directions. Abstract : Metal‐organic framework (MOF) materials and their derivatives have been widely used in electrode materials of lithium/sodium‐ion batteries. However, the study of pristine MOF electrode materials has more important practical significance. This study discusses the effects of different organic ligands and multimetals on the storage performance of MOF‐based lithium/sodium electrodes. Also, the synthetic methods and regulation strategies to improve the conductivity and stability of the pristine MOF electrodes are proposed, which provides an effective reference for the synthesis of materials in the electrochemical field.